2018
DOI: 10.1108/prt-12-2017-0107
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior of aloe vera fiber reinforced epoxy and polyester resin matrix composites

Abstract: Purpose This paper aims to investigate the tensile behavior of epoxy and polyester matrix composites reinforced with continuous and aligned aloe vera fibers. Design/methodology/approach Composites with different volume fractions (30, 40 and 50 Vol. %) were fabricated by laying the fibers in a steel mould and pouring liquid resin, either DEGEBA/TETA epoxy or methyl-ethyl ketone hardened orthophthalic polyester, under pressure of 3 MPa. The specimens were cured for 24 h at room temperature and then tested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These factors include the amount of NaOH, the time spent soaking, and the time spent drying. The optimal condition was determined to be 5.81% NaOH following 3.99 h of soaking and 72 h of drying [14,15]. Experimenting with Taguchi's design approaches provides a simple, effective, and methodical strategy for maximizing experimental settings and determining their impact on process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These factors include the amount of NaOH, the time spent soaking, and the time spent drying. The optimal condition was determined to be 5.81% NaOH following 3.99 h of soaking and 72 h of drying [14,15]. Experimenting with Taguchi's design approaches provides a simple, effective, and methodical strategy for maximizing experimental settings and determining their impact on process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…But some studies show that introduction of aloe vera fibres in polyester or epoxy matrix had a minor effect in improving the strength. 15 Hemp fibre collected from the outer layer or the bast of the Cannabis sativa plant. This fibre conducts heat, dyes easily, blocks ultraviolet light and is seen to have natural anti-bacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…But some studies show that introduction of aloe vera fibres in polyester or epoxy matrix had a minor effect in improving the strength. 15…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al 24 studied the mechanical properties of epoxy resin reinforced by glass fiber in the direction of 0 and 90 , and the study showed that the tensile recovery force in the direction of 90 was the largest. Jenarthanan et al 25 prepared glass fiberreinforced epoxy resin composites by handpaste. The results showed that the mechanical properties of Eglass fiber-reinforced epoxy resin composites were superior to other reinforced composites.…”
mentioning
confidence: 99%
“…Jenarthanan et al. 25 prepared glass fiber-reinforced epoxy resin composites by handpaste. The results showed that the mechanical properties of E-glass fiber-reinforced epoxy resin composites were superior to other reinforced composites.…”
mentioning
confidence: 99%